The Four Mindsets - Mackay, Anna-Lucia (Ascent Audio, 2017)
Connect, focus, align, and activate your team to increase performance fast The Four Mindsets: How to Influence, Motivate, and Lead High Performance Teams holds the key to significantly increasing productivity, performance, and revenue in your organisation. Developed as a guide proven to help all levels of managers to connect, focus, align and activate their teams to elevate results, this audiobook also serves as a low-cost, first step, alternative to expensive training, coaching and mentoring programs by providing a range of resources and tools to use and become a 'best in class' leader today. Management, motivations and mindsets have changed considerably in the last 25 years and leaders are being challenged with the task of keeping their teams engaged while meeting goals that are more stringent than ever before. The High Performance Mindset Model will equip you with the skills you need to take your teams performance to the next level and considers hot topics in today's business environment, such as emotional intelligence, whole brain thinking, and what makes professionals tick, in a format that is applicable at all levels of management and leadership. The Four Mindsets updates you on what matters most today and the most common strategies and techniques used by high performing companies, leaders and managers-globally. Explore the simplest, fastest ways to increase productivity, performance, and revenue. Understand what you must do to be within the top five percent of today's managers. Discuss what makes people tick at work and how this understanding is the number one key to influencing accountability, focus and results. Consider current best practices in team management, and understand how to practically apply these concepts. The Four Mindsets: How to Influence, Motivate, and Lead High Performance Teams is the ultimate handbook for every manager -from team leader to CEO-HR professionals, management consultants, trainers, coaches, and mentors charged with the responsibility of developing today's modern leaders.